The Mid-Term Forecast Method of F10.7 Based on Extreme Ultraviolet Images - L. Lei; Q. Zhong; J. Wang; L. Shi; S. Liu (Advances in Astronomy)
The solar radio flux at 10.7cm (F10.7) is a direct monitor and an important indicator of solar variability, and F10.7 is commonly used in empirical atmospheric models, ionosphere models, etc. The source regions of F10.7 are mainly in the corona above the active regions, and the extreme ultraviolet (EUV) images reflect the coronal thermal structure. In this paper, an index is defined as PSR based on the intensity values of solar EUV images to represent the coronal contribution to F10.7. The Spearman correlation coefficient between the observed values of F10.7 and PSR is 0.85 in 304 Å EUV images. Based on the high correlation, an empirical model is constructed. Combining the EUV data of SDO/AIA and the twin STEREO/EUVI, solar full-disk EUV images can be generated, and the future 27-day values of PSR can be calculated. Then, a realistic estimation of F10.7 from 1 to 27 days in advance can be provided by the empirical model. Compared to the predictive values of F10.7 by the 54th-order autoregressive models in 2012-2013, the error drop-rate of our model is 12.54%, and our method has significant advantages in the upcoming 3 to 27 days’ forecast.